Analysis of the Influence of Consumer Animosity, Religiusity, and Social Media Sentiment on Product Boycott Decisions - Prastiwi, Anis; Harsoyo, Titik Desi (East Asian Journal of Multidisciplinary Research, 2025)
This study examines the impact of Consumer Animosity, Religiosity, and Social Media Sentiment on Product Boycott Decisions. Using purposive sampling, data were collected from 100 respondents who were aware of Boycott campaigns against pro-Israel products and actively use social media. The research employed a questionnaire to gather data, which was tested for validity and reliability. Classical assumption tests confirmed that the data were normally distributed and free from multicollinearity and heteroscedasticity. The findings reveal that Consumer Animosity, Religiosity, and Social Media Sentiment each have a positive and significant effect on Product Boycott Decisions. These results suggest that these factors play a crucial role in shaping consumer behavior in Boycott campaigns.